Secondary Metabolites of the Cuticular Abdominal Glands of Variegated Grasshopper (Zonocerus variegatus L.). (7th September 2015) - Igwe, O. U.; Udofia, D. E.
Abstract : Chemical compounds were extracted with petroleum ether from the cuticular abdominal glands of grasshopper ( Zonocerus variegatus L.) and eleven compounds were characterised using Gas Chromatography/Mass Spectrometry (GC/MS) technique in combination with Fourier Transform-Infrared Spectroscopy (FT-IR). The compounds analysed were 2, 7-dimethyloctane (3.21%), decane (5.33%), undecane (3.81%), tridecanoic acid methyl ester (4.76%), hexadecanoic acid (9.37%), 11-octadecenoic acid methyl ester (23.18%), pentadecanoic acid, 14-methyl-methyl ester (4.43%), (Z)-13-docosenoic acid (10.71%), dodecyl pentafluoropropionate (9.52%), 2-dodecyl-1, 3-propanediol (6.38%), and 1, 12-tridecadiene (19.30%). FT-IR analysis of the extract showed peaks at 1270.17 (C–O and C–F), 1641.48 (C=C), 2937.68 (C–H), and 3430.51 (O–H) cm −1 indicating the presence of ether, alkene, alkane, alcohol, carboxylic acid, and fluoric compounds. These compounds consisted of 32.37% ester, 31.65% hydrocarbons, 20.08% fatty acid, 9.52% halogenated ester, and 6.38% alcohol. The highest component was 11-octadecenoic acid methyl ester followed by 1, 12-tridecadiene. Since behavioural bioassays were not carried out, the consideration of these compounds to be pheromone semiochemicals remains a hypothesis.